Plastic antibody for the diagnosis of acute myocardial infarction - Ricardo, Jacinta (2024)
(Introduction) Myoglobin (Myo) is the first cardiac biomarker to be released into the bloodstream after the onset of symptoms of Acute Myocardial Infarction (AMI), allowing earlier detection of this disease. Novel application based on Plastic Antibody that responds to a cardiac biomarker, Myo. Imprint stage with electropolymerization of ortho-phenylenediamine (OPD) in the presence of Myo. Template removal from polymeric matrix digested by trypsin. The biomimetic film was fabricated on platinum screen-printed electrodes (Pt-SPE) modified with electroactive Prussian blue nanocubes (PBNCs).